Gender equality and parenting-related leaves in 21 former socialist countries - Dobrotic, I; Stropnik, N (Emerald, 2020)
Purpose: This article explores the patterns and dynamics of parenting-related leave policy reforms in the European former socialist countries (EFSCs). It sheds light on the development pattern of their leave policies and their potential to reproduce, impede, or transform traditional gender norms in employment and care.